The Effect of Tax Service Quality, Taxpayer Awareness, and Tax Incentives on Msme Taxpayer Compliance in Binjai City - Sulist Yowati Yuswadi Buulolo; Miftah Rizkina (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to find the influence of the quality of tax services, taxpayer awareness, and tax incentives on the compliance of MSME taxpayers in Binjai City. The population in this study is not known for sure, but the number of samples taken was 96 respondents calculated using the Lemeshow formula. This study uses primary-quantitative data collected through questionnaires and then processed with the SPSS Version 24 application. The analysis technique used is multiple linear regression analysis. The results of the study show that the quality of tax services, taxpayer awareness, and tax incentives both partially and simultaneously have a positive and significant effect on taxpayer compliance in MSMEs in Binjai City. The quality of tax services has a regression value of 0.301, a calculation of 3.327 with a significance of 0.001. Taxpayer awareness has a regression value of 0.334, tcalculation of 3.826 with a significance of 0.000. Tax incentives have a regression value of 0.238, a calculation of 3.042 with a significant value of 0.003. The results of the F test showed an F value of 108.094 with a significance of 0.000. The value of the table is 1.986 and the table F is 2.704 so that the tcount of > tof the table and the Fcount > Ftable with a significant < 0.05, then accept Ha and subtract Ho which means that there is a significant influence. This shows that the hypotheses H1, H2, H3, and H4 are acceptable and proven to be true because the results of the research are in line with the hypothesis proposed. The most dominant variable influencing taxpayer compliance is the variable of taxpayer awareness with the largest calculation. Around 77.2% of taxpayer compliance can be explained and obtained from the quality of tax services, taxpayer awareness, and tax incentives, while the rest is obtained from other factors. Taxpayer compliance has a very strong relationship with the quality of tax services, taxpayer awareness, and tax incentives.